DESIGNING 360-DEGREE VIDEO-BASED JOURNALISTIC CONTENT: AN ANALYSIS OF NEEDS AND CHALLENGES - Reza Saeful Rachman; Daniel Paulus Evert; Nina Lestari; Tanto Trisno Mulyono (PT Altin Riset Publishing, 2026)
Digital transformation is driving mass media to adopt more interactive news formats, one of which is immersive journalism based on 360° video. This study aims to analyze the needs and challenges of developing 360° journalistic content by linking three theoretical foundationsaffordance, presence, and journalistic ethics to formulate an effective design approach. The method used is the 4D R&D model (Define, Design, Develop, Disseminate) with a mixed approach: a questionnaire to map public interest and perception, a literature review to map the latest technical ethical findings, and in-depth interviews with journalists to understand industry needs, production constraints, and technology adoption strategies. The results show a growing demand for 360° content; journalists consider this format to open up opportunities for richer and more empathetic storytelling, while 85% of audience respondents expressed interest in trying/watching 360° content due to the more immersive experience and navigation control. However, significant barriers include device and training costs, post-production complexity, reliance on network infrastructure, adoption challenges for older users (approximately 30% report dizziness/difficulty wearing VR headsets), and ethical risks associated with potential emotional manipulation. This study proposes a 360° prototype design framework that integrates affordance (free navigation, rotation, and visual focus), presence enhancement for cognitive empathy, and ethical guidelines (transparency of source, context, and privacy). Practical implications include the need for technical training, funding support, and cross-platform dissemination strategies for more inclusive adoption.